Looking at a class of RFID APs through GNY logic. (19th March 2010) - Zhang, Xiaowen; Gao, Qinghai; Saad, Mohamed K.
Radio Frequency Identification Authentication Protocols (RFID APs) are an active research topic and many protocols have been proposed. In this paper, we consider a class of recently proposed lightweight RFID authentication protocols: CRAP, LCAP, OHLCAP, O-TRAP, YA-TRAP, and YA-TRAP+, which are claimed to be resistant to conventional attacks and suitable for low cost RFID device scenarios. We examine them using GNY logic to determine whether they can be proved to have achieved their protocol goals. We show that most of them meet their goals, though some do not. Furthermore this approach enables us to identify similarities and subtle differences among these protocols. Finally, we offer guidelines on when it is necessary to use encryption rather than hash functions in the design of RFID authentication protocols.